Bibliometric Analysis Using VOSViewer with Publish or Perish of Metacognition in Teaching English Writing to High School Learners - Damkam, Tanadon; Chano, Jiraporn (Bumi Publikasi Nusantara, 2024)
The purpose of the research was to analyze the research trends in exploring metacognition in teaching English writing to high school students. The methods used in this research were bibliometric analysis methods with VOSviewer analysis. The data were collected from research articles from the Google Scholar database, published between 2018 and 2024. According to the research results, the total documents found during the period were 199 articles. It was found that there was a decrease in the number of articles in 2019, but then it increased in 2022. However, the amount of research articles dropped in 2024. Mapping article data creates three forms of visualization; including network, overlay, and density visualization. The result of mapping reveals that research on metacognition in teaching English writing needs to be carried out, especially regarding teaching to high school students. This research concluded that the trend of research investigating metacognition in teaching English writing to high school students is decreasing, nevertheless its importance in assisting English language pedagogy.